PENGOLAHAN PRODUK GEDEBONG CHIPS SEBAGAI UPAYA MENGEMBANGKAN POTENSI DESA UNTUK MEWUJUDKAN KEWIRAUSAHAAN INOVATIF di DESA LELEDE - Basit, Akram Mukdial; Hidayati, Diah; Putri, Baiq Wahyu Anindia; Agustina, Firda Hasnawati; Sholitiah, Aulia Ismy; Mariana , Dina; Suryana, Baiq Amami; Maulina, Ade Qory; Fibriyanti, Dinda; Norasikin, Norasikin (Jurnal Wicara Desa, 2023)
By looking at the climatic conditions in Lelede Village, the potential for natural resources is quite abundant, one of which is banana trees. The potential possessed by Lelede Village in this matter can be a great opportunity as one of the businesses that can be developed for Lelede Village in improving the economy and people's standard of living, namely making Gedebong Chips. Student involvement in the community is expected to be able to take advantage of the potential that exists in Lelede Village. One effort that can be developed from village potential is making gedebong chips from banana tree trunks. For this reason, the University of Mataram KKN FKIP team is a solution in maximizing the utilization of potential in Lelede Village, Kediri District, West Lombok Regency.